TEACHERS’ OPINION ON EFFECTIVENESS OF INDUCTIVE AND DEDUCTIVE METHOD FOR SECONDARY STUDENTS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Instructional teaching approach matters in classroom teaching. Generally in our classroom the teachers use two distinct approaches that are inductive and deductive. Teachers have a good idea that which method impacts more in learning. The study was done with three relevant objectives. A small sample of Govt. Aided school teachers of New Barrakpur, West Bengal was taken in the study. Researcher personally interviewed the teachers. Data were analyzed in both qualitative and quantitative form. According to the objectives the findings has come in all the way that students like more inductive method than deductive method and inductive method is more effective for the secondary students.